Territory and Frontier Defence Systems: The Project of Isidro Próspero Verboom for the Fortification of San Sebastián in 1726 - Víctor ECHARRI IRIBARREN (Studia Historica: Historia Moderna, 2018)
The modernising of the fortifications on the French-Spanish border was a priority for the Borbon monarchs. In 1725 Jorge Próspero Verboom, accompanied by his son Isidro Próspero, moved to Pamplona. From there he directed the projects for the fortification of San Sebastián, Pamplona and Fuenterrabía. He entrusted Isidro with drawing up the project for San Sebastián, using this as a way of ensuring that he would succeed him in the post of Engineer General. The project consisted of thirty seven plans, the most extensive of any drawn up in the history of Spanish fortifications. This research analyses the technical aspects of it. In addition to repairing the breaches in the siege of 1719, Isidro Próspero Verboom strengthened the defences at strategic points, and established an ambitious system of batteries at the top of Mount Urgull. In this way he gave the square in front of Fuenterrabía an important defensive role, although the investment was much less than that destined for Pamplona.